Ex-Vivo Dynamic 3-D Culture of Human Tissues in the RCCS™ Bioreactor Allows the Study of Multiple Myeloma Biology and Response to Therapy - Ferrarini, Marina; Steimberg, Nathalie; Ponzoni, Maurilio; Belloni, Daniela; Berenzi, Angiola; Girlanda, Stefania; Caligaris-Cappio, Federico; Mazzoleni, Giovanna; Ferrero, Elisabetta (PloS one, 2013)
Three-dimensional (3-D) culture models are emerging as invaluable tools in tumor biology, since they reproduce tissue-specific structural features and cell-cell interactions more accurately than conventional 2-D cultures. Multiple Myeloma, which depends on myeloma cell-Bone Marrow microenvironment interactions for development and response to drugs, may particularly benefit from such an approach. An innovative 3-D dynamic culture model based on the use of the RCCS™ Bioreactor was developed to allow long-term culture of myeloma tissue explants. This model was first validated with normal and pathological explants, then applied to tissues from myeloma patients. In all cases, histological examination demonstrated maintenance of viable myeloma cells inside their native microenvironment, with an overall well preserved histo-architecture including bone lamellae and vessels. This system was then successfully applied to evaluate the cytotoxic effects exerted by the proteasome inhibitor Bortezomib not only on myeloma cells but also on angiogenic vessels. Moreover, as surrogate markers of specialized functions expressed by myeloma cells and microenvironment, β2 microglobulin, VEGF and Angiopoietin-2 levels, as well as Matrix Metalloproteases activity, were evaluated in supernatants from 3D cultures and their levels reflected the effects of Bortezomib treatment. Notably, determination of β2 microglobulin levels in supernatants from Bortezomib-treated samples and in patients'sera following Bortezomib-based therapies disclosed an overall concordance in the response to the drug ex vivo and in vivo. Our findings indicate, as a proof of principle, that 3-D, RCCS™ bioreactor-based culture of tissue explants can be exploited for studying myeloma biology and for a pre-clinical approach to patient-targeted therapy.